Current indications and results of orthotopic ileal neobladder for bladder cancer. Issue 4 (April 2014) - Minervini, Andrea; Serni, Sergio; Vittori, Gianni; Masieri, Lorenzo; Siena, Giampaolo; Lanciotti, Michele; Lapini, Alberto; Gacci, Mauro; Carini, Marco
Abstract : During the past three decades, the reconstructive aspects of urologic surgery emerged and became a major component of our surgical specialty, and the most relevant developments have been observed in the field of urinary diversions. Health-related quality of life and self esteem have been improved following orthotopic bladder substitutions, which are actually the preferred method for continent urinary diversion. Patients with neobladders have enhanced cosmesis and the potential for normal voiding function with no abdominal stoma. Patient's selection for orthotopic neobladder formation is mandatory as most of the surgical complications or consequences associated with a neobladder are correlated not only with surgical technique or management after surgery, but also with wrong patient's selection. The principles of intestinal detubularization and reconfiguration to obtain spherical reservoir are the basis of continent urinary diversions and ileum seems to be preferable over any other segment. Nowadays, ileal neobladder is a widely adopted solution after cystectomy with a neobladder rate of 9–19% for population-based data with an increase to 39.1–74% for high-volume centers. However, controversies still exist in this urological field about the best candidates for neobladder construction, the best type of neobladder to offer, whether or not an antireflux uretero intestinal anastomosis should be used, the future of minimally invasive approaches, that is, robotic assisted cystectomy plus extracorporeal or intracorporeal neobladder, and last but very important, the functional results and the level of symptoms-induced distress and quality of life in the long term in patients with bladder cancer receiving an orthotopic bladder substitution. All these issues are discussed on the basis of the most recent published data.